STUDY OF SOLUBILITY OF SYSTEMS: POTASSIUM SALT- MONOSUBSTITUTED ACETIC ACID ETHANOLAMMONIUM-WATER. - M.T. Abdullayeva; I.M. Tojiboyeva (Western European Studies, 2023)
The solubility polymeter in the system К2SO4–CH3COOH· H2NC2H4OH–H2O was studied using eight internal sections. A diagram was constructed based on the solubility polymeter of binary systems and eight internal sections. The mutual influence of components in the system СН3СООН·H2NC2H4OH–KCI–H2O, studied by the method of isomolar series, revealed branches of the existence of initial components and new chemical compounds on the temperature crystallization isotherms, viscosity, density, and pH of the medium. The studied system belongs to the simple eutonic type with the preservation of the individuality of the constituent components.
Keywords: Physiologically; binary; liquid; potassium